THE EFFECT OF MUROTTAL AL-QUR'AN THERAPY ON PAIN IN POST-SECTION CAESAREAN PATIENTS WITH SPINAL ANESTHESIA - Umi Sakdiyah; Wilis Sukmaningtyas; Dwi Novitasari; Daryanto; Awal Tunis Yantoro (PT. Radja Intercontinental Publishing, 2026)
Pain in post-caesarean section patients with spinal anesthesia remains a major problem that can hinder maternal recovery, early mobilization, and breastfeeding. This study aims to determine the effect of Quranic recitation therapy on pain in post-caesarean section patients with spinal anesthesia at Banjarnegara Islamic Hospital. This study used a quantitative method with a pre-experimental one-group pretest-posttest design. The study population consisted of all post-caesarean section patients at Banjarnegara Islamic Hospital, with a sample of 40 respondents selected using purposive sampling. The research instruments included a Numerical Rating Scale and a respondent characteristics sheet. Data analysis was performed using a paired sample t-test. The results showed that the average pain level before the intervention was in the moderate pain category, while after the intervention it decreased to the mild pain category. There was a significant effect of Quranic recitation therapy on reducing pain in post-caesarean section patients with spinal anesthesia. In conclusion, Quranic recitation therapy is effective as a non-pharmacological intervention for reducing postoperative pain.